(untitled) (Research, Society and Development, 2021)
The styloid process of the temporal bone is a bone projection which is localized anteriorly to the stylomastoid foramen, in between the internal and external carotid arteries, and posteriorly to the pharynx The normal average length of the styloid process is 20 to 30 mm. The aim of this study was to evaluate the average lengths of the styloid process in patients who underwent panoramic radiographs in a private clinic.A sample calculation was conducted to define the minimum size needed to represent the entire state of Ceará, Brazil. After establishing a confidence level of 95% and a 5% margin of error, a minimum of 385 panoramic radiographs was determined based. Following inclusion and exclusion criteria, at the end 503 panoramic radiographs were included. In order to evaluate the associations between styloid process lengths and gender/age. Elongated styloid process was found in 56% of the radiographies of male patients and in 41% of the ones of female patients. The mean average of styloid process length was 33.51 mm for male and 31.17 mm for female patients. The relationship between the length of the styloid process and age was significant only if the right side was considered. The inter and intra-examiner calibration was evaluated by the Kappa Test. The data normality of the errors was evaluated using the Shapiro-Wilk’s Test. Then, the data were analyzed with ANOVA, Student’s T-test and Chi-squared Test. Among all participants, 46.2% exhibited elongated styloid processes based on their respective radiographs.